THE ROLE OF MUSIC EDUCATION IN CHILD DEVELOPMENT: A PEDAGOGICAL PSYCHOLOGICAL PERSPECTIVE - Abdulhay Karimov (Bright Mind Publishing, 2025)
This article explores the pedagogical and psychological dimensions of music education in the context of child development. It emphasizes the role of music-based lessons and activities in shaping children's intellectual, emotional, and moral growth. Drawing on educational theory and developmental psychology, the study highlights how structured engagement with music can enhance cognitive functions, foster emotional intelligence, and instill ethical values. The findings underscore music’s potential as a holistic educational tool for nurturing well-rounded, creative, and socially responsible individuals.
Keywords: Children, folklore, creativity, games, dance, singing, stage, culture, genre, education, goal, process, works, features, similarity, difference.